The effect of competence, workload, and incentives on the interest of civil servants to become commitment-making officials in Malaka Regency - Emanuel Rikhardus Seran; Petrus Kase; Nursalam Nursalam (Goodwood Publishing, 2022)
Purpose: This study aimed to determine the influence of individual competence, workload, and incentives on the interest of State Civil Servants for the positions of Commitment-Making Officials in Malaka Regency. Research Methodology: The type of method in this research is quantitative research method. The sampling techniques used are Non-probability Sampling method and Saturated Sampling technique. The data analysis techniques are simple linear regression and multiple linear analyses. Results: The results of this study are that partially, individual competence, workload, and incentives have a positive but not significant effect on the interest of civil servants in the Commitment-Making Official Positions in Malaka Regency. Individual competence, workload, and incentives simultaneously have a positive and significant effect on the interest of civil servants in commitment-making positions in Malaka Regency. Conclusions: The study shows that while individual competence, workload, and incentives have a positive but insignificant effect on the interest of State Civil Servants in Commitment-Making Official positions, together they significantly influence their interest in these roles. Limitations: Research variables are complex and research results may change in the future. Contributions: The findings of this study can be used as the basis for evaluating the Malaka local government bureaucracy and can be scientific information for students of the public administration program.